Genetic Detection of Lint Percentage Applying Single-Locus and Multi-Locus Genome-Wide Association Studies in Chinese Early-Maturity Upland Cotton - Su, Junji; Wang, Caixiang; Hao, Fushun; Ma, Qi; Wang, Ji; Li, Jilian; Ning, Xinzhu (Frontiers in Plant Science, 2019)
Upland cotton (Gossypium hirsutum L.) is the most important source of natural fiber in the world. Early-maturity upland cotton varieties are commonly planted in China. Nevertheless, lint yield of early-maturity upland cotton varieties is strikingly lower than that of middle- and late-maturity ones. How to effectively improve lint yield of early maturing cotton becomes a focus of cotton research. Here, based on 72,792 high-quality single nucleotide polymorphisms (SNPs) of 160 early-maturing upland cotton accessions, we performed genome-wide association studies (GWAS) for lint percentage (LP), one of the most lint-yield component traits, applying one single-locus method and six multi-locus methods. A total of 4 and 45 significant quantitative trait nucleotides (QTNs) were respectively identified to be associated with LP. Interestingly, in two of four planting environments, two of these QTNs (A02_74713290 and A02_75551547) were simultaneously detected via both one single-locus and three or more multi-locus GWAS methods. Among these 42 genes within a genomic region (A02: 74.31-75.95 Mbp) containing the above two peak QTNs, Gh_A02G1269, Gh_A02G1280 and Gh_A02G1295 had the highest expression levels in ovules during seed development from 20 and 25 days post anthesis (DPA), whereas Gh_A02G1278 preferentially expressed in the fibers rather than other organs. These results imply that the four potential candidate genes might be closely related to cotton LP by regulating the proportion of seed weight and fiber yield. The QTNs and potential candidate genes for LP identified in this study provide valuable resource for cultivating novel cotton varieties with earliness and high lint yield in the future.